DAMPAK PELECEHAN SEKSUAL TERHADAP ANAK USIA DINI DAN UPAYA PENANGANANNYA DALAM PERSPEKTIF PEKERJAAN SOSIAL - Arini Sisi Nabillah (Lembaran Masyarakat: Jurnal Pengembangan Masyarakat Islam, 2019)
Cases of early childhood sexual abuse are cases that are familiar to the wider community. Cases like this often roam in print and electronic media, and many are still not exposed in the public sphere. This can occur for several reasons. Children tend not to tell the incident to their parents, and even parents are less sensitive to the strangeness of their children. The result can cause various unwanted effects. Various methods are used to minimize cases of sexual abuse against early childhood. The method in this article uses literature review. The purpose of this article is to determine the impact and efforts to deal with sexual abuse against early childhood through the perspective of social workers. The results in this article are to find out the effects of early childhood abuse on sexual harassment cases, as well as efforts to address them through the perspective of social workers.